2017
DOI: 10.1093/mnras/stx2786
|View full text |Cite
|
Sign up to set email alerts
|

RoboPol: connection between optical polarization plane rotations and gamma-ray flares in blazars

Abstract: We use results of our 3 year polarimetric monitoring program to investigate the previously suggested connection between rotations of the polarization plane in the optical emission of blazars and their gamma-ray flares in the GeV band. The homogeneous set of 40 rotation events in 24 sources detected by RoboPol is analysed together with the gamma-ray data provided by Fermi-LAT. We confirm that polarization plane rotations are indeed related to the closest gamma-ray flares in blazars and the time lags between the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 43 publications
8
78
0
2
Order By: Relevance
“…For rotation-dominated epochs with the helical B fields we can instead associate dx ch with the timescale of a typical observed optical rotation, roughly 360 • per month (Blinov et al 2018), so we take dx ch ≈ 1dc/β. For many typical blazar parameters these stochastic and he-lical characteristic length scales are of similar size.…”
Section: Light Travel Effectsmentioning
confidence: 99%
“…For rotation-dominated epochs with the helical B fields we can instead associate dx ch with the timescale of a typical observed optical rotation, roughly 360 • per month (Blinov et al 2018), so we take dx ch ≈ 1dc/β. For many typical blazar parameters these stochastic and he-lical characteristic length scales are of similar size.…”
Section: Light Travel Effectsmentioning
confidence: 99%
“…At this time, the variability behavior of the radio emission may only be related to the local variation of downstream extended radio emission region. Recent studies have found that in some blazars, their γ-ray emission is associated with their optical polarization degree and the rotation of PA (see, e.g., Itoh et al 2016;Blinov et al 2018). Since the ambiguity of the PA can not be completely eliminated (see Section 3.1 above), here we only analyze the cross-correlation between the po-larization degree and the γ-ray emission.…”
Section: Multiwavelength Correlationsmentioning
confidence: 99%
“…Large EVPA rotations have been observed that are sometimes correlated with flares detected at γ-rays (e.g. Blinov et al 2018). The picture appears quite complex, as changes in the jet viewing angle can mimic a stochastic process even when the variations in flux and P , and EVPA rotations, are produced by a deterministic process (Lyutikov & Kravchenko 2017).…”
Section: Polarimetric Observationsmentioning
confidence: 99%